Does Board Ethnic Diversity Impact Board Monitoring Outcomes?. (30th January 2019) - Guest, Paul M.
Abstract: This study investigates whether board ethnic diversity is associated with stronger board monitoring outcomes. We explore a range of outcomes – CEO compensation, accounting misstatements, CEO turnover–performance sensitivity and acquisition performance – but find no evidence to support this. We also find no evidence that board ethnic diversity improves overall firm performance, even for those firms with higher agency problems. Our results are robust across different methodologies and have important practical implications, by informing the current public policy debate on board ethnic diversity.